Practices of human resources management in small businesses - Moreno, Diana Cristina Rodríguez (Universidad Pedagógica y Tecnológica de Colombia, 2012)
While most of the knowledge concerning traditional human resources topics (recluting, selection, training, performance management and compensation) is for large companies, evidence suggests that human resources practices in small companies are different. This paper contrasts research in human resources management in small firms of different countries finding important similarities.